Betty Friedan and the making of The feminine mystique : the American left, the cold war, and modern feminism - Horowitz, Daniel, 1938- (Amherst : University of Massachusetts Press, 1998)
"Drawing on an impressive body of new research - including Friedan's own papers - Horowitz traces the development of Friedan's feminist outlook from her childhood in Peoria, Illinois, through her wartime years at Smith College and Berkeley, to her decade-long career as a writer for two of the period's most radical labor journals, the Federated Press and the United Electrical Workers' UE News. He further shows that even after she married and began to raise a family, Friedan continued during the 1950s to write and work on behalf of a wide range of progressive social causes." "By resituating Friedan within a broader cultural context, and by offering a fresh reading of The Feminine Mystique against that background, Horowitz not only overturns conventional ideas about "second-wave" feminism but also reveals long submerged links to its past."--Jacket.
1. Peoria, 1921-38 -- 2. Bettye Goldstein at Smith College, 1938-40: An Education in Creativity, Psychology -- and Politics -- 3. The Radicalization of Bettye Goldstein, 1940-41 -- 4. It All Comes Together, 1941-42: Anti-Fascism, Women Workers, Unions, War, and Psychology -- 5. A Momentous Interlude: Berkeley, 1942-43 -- 6. Federated Press, 1943-46: Popular Front Labor Journalist -- 7. UE News, 1946-52: Workers, Women, and McCarthyism -- 8. The Personal Is Political, 1947-63 -- 9. Free-lance Writer, 1952-63 -- 10. The Development of The Feminine Mystique, 1957-63 -- 11. 1963 to the Present.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Friedan, Betty; Friedan, Betty; Friedan, Betty; Friedan, Betty, -- (1921- ...); Feminists -- United States -- Biography; Feminism -- United States; United States -- Politics and government -- 20th century; Féministes -- États-Unis -- Biographies; Féminisme -- États-Unis.; États-Unis -- Politique et gouvernement -- 20e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; SOCIAL SCIENCE -- Feminism & Feminist Theory; Feminism; Feminists; Politics and government; United States; Gender & Ethnic Studies; Social Sciences; Gender Studies & Sexuality; Féministes -- États-Unis -- Biographies; Féminisme -- États-Unis -- Histoire; États-Unis -- Politique et gouvernement -- 20e siècle.; 1900-1999; Biographies